2019
DOI: 10.3390/nu12010005
|View full text |Cite
|
Sign up to set email alerts
|

Current Data on Dietary Sodium, Arterial Structure and Function in Humans: A Systematic Review

Abstract: Background: Subclinical arterial damage (SAD) (arteriosclerosis, arterial remodeling and atheromatosis) pre-exists decades before cardiovascular disease (CVD) onset. Worldwide, sodium (Na) intake is almost double international recommendations and has been linked with CVD and death, although in a J-shape manner. Studies regarding dietary Na and major types of SAD may provide pathophysiological insight into the association between Na and CVD. Objectives: Systematic review of data derived from observational and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
(242 reference statements)
0
6
0
Order By: Relevance
“…With both adults and children consuming well above the recommended intake of sodium, there is the potential for dietary interventions to make a substantial impact. Trials in adults have shown that dietary sodium reduction decreases arterial stiffness [53] and central aortic BP [54] and also improves carotid artery compliance, among those with and without preexisting hypertension. With sodium intake associated with cardiovascular effects in childhood, intervening to reduce sodium intake even earlier in the lifespan holds promise for even greater downstream cardiovascular benefits.…”
Section: Discussionmentioning
confidence: 99%
“…With both adults and children consuming well above the recommended intake of sodium, there is the potential for dietary interventions to make a substantial impact. Trials in adults have shown that dietary sodium reduction decreases arterial stiffness [53] and central aortic BP [54] and also improves carotid artery compliance, among those with and without preexisting hypertension. With sodium intake associated with cardiovascular effects in childhood, intervening to reduce sodium intake even earlier in the lifespan holds promise for even greater downstream cardiovascular benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the incorporation of genetic or environmental factors associated with salt-sensitivity are needed to further clear this field. Finally, it is important to conduct prospective RCTs that will examine the long-term effects of dietary Na intake on cardiovascular morbidity/mortality, including at least three levels of daily Na intakes (very low, 'normal', and high) as very low dietary Na diets have been suggested to associate with subclinical vascular damage in both human [97,98] and animal studies [99][100][101][102]. Moreover, considering the large variety of potentially confounding factors related to dietary intake and cardiovascular parameters, future studies should secure that all of them are wellcontrolled and reliably assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, over the years this hypothesis has become even more intriguing because: (i) of the presence of a J-shape association between daily sodium intake and mortality in epidemiological studies [ 18 , 19 , 20 ], (ii) both very high and very low sodium intake are implicated in the pathogenesis of arterial damage [ 5 , 21 , 22 , 23 , 24 ], (iii) data derived from in vitro and in vivo experimental animal studies, as well as preliminary human studies, suggest an association between high sodium intake and autoimmune disease [ 25 ], and finally (iv) not only high, but also very low sodium intake seems to be proinflammatory [ 26 , 27 ]. However, given the fact that other factors (including certain types of foods, sedentary life, sleep apnea) [ 28 , 29 ] may have proinflammatory effects, the task to delineate and quantify the potential effects of sodium intake on systemic inflammation is quite complex.…”
Section: Introductionmentioning
confidence: 99%